2012
DOI: 10.5194/ms-3-63-2012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental investigation of process parameters in WEDM of WC-5.3 % Co using response surface methodology

Abstract: Abstract. Tungsten carbide-cobalt (WC-Co) composite is a difficult-to-machine material owing to its excellent strength and hardness at elevated temperature. Wire electrical discharge machining (WEDM) is a best alternative for machining of WC-Co composite into intricate and complex shapes. Efficient machining of WC-Co composite on WEDM is a challenging task since it involves large numbers of parameters. Therefore, in present work, experimental investigation has been carried out to determine the influence of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The designs for fitting response surfaces are called response surface designs. The objective of RSM is to determine to determine a region of the factor space in which operating requirements are satisfied or the optimum operating conditions for the system (Datta and Mahapatra, 2010;Jangra and Grover, 2012;Aggarwal et al, 2015). Analysis of several responses is carried out in RSM.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…The designs for fitting response surfaces are called response surface designs. The objective of RSM is to determine to determine a region of the factor space in which operating requirements are satisfied or the optimum operating conditions for the system (Datta and Mahapatra, 2010;Jangra and Grover, 2012;Aggarwal et al, 2015). Analysis of several responses is carried out in RSM.…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Response surface methodology (RSM) is a collection of mathematical and experimental techniques that requires sufficient number of experimental data to analyse the engineering problem and to develop mathematical models for several input variables and output performance characteristics (Myers & Montgomery, 1995;Jangra & Grover, 2012). By using the design of experiments and applying regression analysis, the modelling of the desired response ( ) to several independent input variables (xi) can be gained.…”
Section: Response Surface Methodology and Experimental Designmentioning
confidence: 99%
“…Dielectric flow rate also increased the MRR initially, up to a certain limit and after that it was decreased because of pronounced cooling effect on the work material. Jangra K. and Grover S. [23] investigated the effect of process parameters (pulse-on-time, pulse offtime, servo voltage, wire feed rate) on cutting rate of WC-5.3%Co composite material during WEDM operation. Results showed that cutting speed increased with increment in pulse on-time and wire feed rate, and it got decreased with increasing pulse off-time and servo voltage.…”
Section: Cutting Ratementioning
confidence: 99%